DINAMIKA KEAMANAN KAWASAN ASIA PASIFIK DALAM PERSAINGAN KEKUATAN MARITIM CHINA DAN AMERIKA SERIKAT - Angga Nurdin Rachmat (Dauliyah Journal of Islamic and International Affairs, 2017)
The security dynamics in Asia Pacific Region are concerned with the interaction of the countries within the region. The interaction between China and the United States is became a recent interesting phenomenon linked to China’s rapid economic and military development. That conditions will have an impact on the balance of power within the region. The United States as a hegemonic force in recent decades saw the development of China’s military power as a catalyst for the instability of the region, seeing that the US re-oriented the defense policy orientation from the Atlantic back to the Pacific. The existence of two countries in an effort to seize dominance in the Pacific will have an impact on the security of the region. Therefore this paper will attempt to discuss the security dynamic of the Asia Pacific region on the rivalry of two super power, US and China. The discussion will be started by analyzing the relationship between the dominance of the inter-regional interaction in the region and make a description of US domination as a major power in Asia Pacific which was rivaled by China through the development of maritime power and will look at US defense policy in response to the development of China’s maritime power in Pacific region, where the rivalry of these two forces is predicted to escalated in conflict in the South China Sea.